2015
DOI: 10.3390/en81010605
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Looping Combustion and Gasification of Coals and Oxygen Carrier Development: A Brief Review

Abstract: Chemical-looping technology is one of the promising CO2 capture technologies. It generates a CO2 enriched flue gas, which will greatly benefit CO2 capture, utilization or sequestration. Both chemical-looping combustion (CLC) and chemical-looping gasification (CLG) have the potential to be used to generate power, chemicals, and liquid fuels. Chemical-looping is an oxygen transporting process using oxygen carriers. Recently, attention has focused on solid fuels such as coal. Coal chemical-looping reactions are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 88 publications
(238 reference statements)
1
70
0
Order By: Relevance
“…However the large supply of coal dictates that investigation into CLC with solid fuels is also important. Indeed, the use of solid fuels has extended during the last years, and an extensive work has been done in the use of solid fuels Wang et al, 2015a;Adanez et al, 2012). When using gaseous fuels, the fuel can be fed directly to the fuel reactor as the fluidization agent.…”
Section: Chemical Looping Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the large supply of coal dictates that investigation into CLC with solid fuels is also important. Indeed, the use of solid fuels has extended during the last years, and an extensive work has been done in the use of solid fuels Wang et al, 2015a;Adanez et al, 2012). When using gaseous fuels, the fuel can be fed directly to the fuel reactor as the fluidization agent.…”
Section: Chemical Looping Combustionmentioning
confidence: 99%
“…However many of these methods increase production costs for the OC and therefore decrease the economic feasibility of such systems (Porrazzo et al, 2016;Abad et al, 2007). The use of raw metal ores has been investigated by numerous groups as a method of providing a readily available and cheap oxygen carrier for the chemical looping process Wang et al, 2015a;Adanez et al, 2012;Imtiaz et al, 2013). The objective of this paper is to compile the latest work involving the use of natural ores as OCs in CLC processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, almost half of reserves in the world are low-rank coal, and there is a policy burden due to the high price of high-rank coal. Therefore, in recent years several efforts have been made to develop technologies for utilizing the relatively inexpensive low-rank coal [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…A wire-heating reactor was used to measure the temperature of low-rank coal char, and a spot-ignition model was suggested for the evaluation of the intrinsic reaction kinetics and the prediction of the ignition temperature [6]. A pressurized wire-heating reactor was also used to predict the gasification kinetics of low-rank coal char in a CO 2 atmosphere. The study indicated that the reaction kinetics were affected by elevated pressure (up to 30 atm) and high temperature (up to 1723 K) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the second step of the process uses air to re-oxidize the oxygen carrier and emits only oxygen depleted air. From an environmental point of view, this technology is innovative and provides energy with greenhouse gas emission-free and even negative contribution for combustion of biomass and biogas [7,8]. The core technologies of CLC processes are fluidized or packed bed reactors.…”
Section: Introductionmentioning
confidence: 99%